THE PRUDENT SOLUTION TO RECOVER THE ECONOMIC DOWNFALL AS DEPIC TED IN LILLIAN HELLMAN’S THE LITTLE FOXES - Poniman Poniman; Melania Lulut Mariani; Muhammad Sirod (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The aims of this research is to describe the problem solution reflected in the drama ‘The Little Foxes’ written by Lillian Hellman, especially dealing with the problems in the South of the United States and the awakening spirit following its economic downfall.. The source of the main data is the text of the drama itself. The supporting data are collected through a librarian research. The data intrinsic and extrinsic data are analyzed and the results are presented descriptively. The findings show that the economic crisis experienced by the Southerners that are symbolized by the characters of ‘The Little Foxes’ was caused by the civil war, the fall of the aristocracy, the ambition of the New Southerners and the influence of the North.. Finally the author offers an alternative solution to overcome the conflicts by presenting Alexandra, who represents a young generation to realize a wise strategy of solving problems. She adopts aristocratic values that appreciate and respect very much humanity and justice, and at the same time she step forward confidently, facing the challenges as well as the opportunity of the new era. Alexandra is the symbol of an alternative solution. Key words: problems, economic downfall, awakening spirit.